PREVALENSI KARIES GIGI POSTERIOR BERDASARKAN KEDALAMAN, USIA DAN JENIS KELAMIN DI RSGM FKG UNAIR TAHUN 2014 (Prevalence of Posterior Teeth Caries by The Depth of Cavity, Age and Gender at RSGM FKG UNAIR in 2014) - Amelia Kristanti Rahardjo Rahardjo; Ira Widjiastuti; Edhie Arif Prasetyo (Conservative Dentistry Journal, 2016)
Background. Dental caries is one of the most prevalent chronic disease of people worldwide, and also Indonesia. Based on Indonesian Basic Research from  Health Department, prevalence of dental caries in Indonesia was 90.5%. When dental caries rates are reported by gender, female are found to exhibit higher prevalence rates than male. Dental caries is disease of lifetime because it can spread out more throughout life and will continue until the teeth are destroyed without a proper treatment.  Purpose. The aim of this study is to analyze the prevalence of posterior teeth caries by the depth of cavity, age, and gender at RSGM FKG UNAIR.  Method. Analytic observational study with cross-sectional and stratified random sampling method. Result. Out of 420 patients with teeth caries, 169 male patients (40.2 %) and 251 female patients (59.8 %). The highest prevalence is deep caries (59.76%) and the lowest prevalence is superficial caries (15.95%). Conclusion. It was concluded that there is  correlation between the depth of cavity increase by age and female has higher caries prevalence than male but no significance differences between cavity depth and gender.